Selection on female remating interval is influenced by male sperm competition strategies and ejaculate characteristics. - Alonzo, S; Pizzari, T (2013)
Female remating rate dictates the level of sperm competition in a population, and extensive research has focused on how sperm competition generates selection on male ejaculate allocation. Yet the way ejaculate allocation strategies in turn generate selection on female remating rates, which ultimately influence levels of sperm competition, has received much less consideration despite increasing evidence that both mating itself and ejaculate traits affect multiple components of female fitness. Here, we develop theory to examine how the effects of mating on female fertility, fecundity and mortality interact to generate selection on female remating rate. When males produce more fertile ejaculates, females are selected to mate less frequently, thus decreasing levels of sperm competition. This could in turn favour decreased male ejaculate allocation, which could subsequently lead to higher female remating. When remating simultaneously increases female fecundity and mortality, females are selected to mate more frequently, thus exacerbating sperm competition and favouring male traits that convey a competitive advantage even when harmful to female survival. While intuitive when considered separately, these predictions demonstrate the potential for complex coevolutionary dynamics between male ejaculate expenditure and female remating rate, and the correlated evolution of multiple male and female reproductive traits affecting mating, fertility and fecundity.